Sex hormones and genetic variants in hormone metabolic pathways associated with the risk of colorectal cancer. (April 2020) - Li, Shuwei; Chen, Yehua; Xie, Lisheng; Meng, Yixuan; Zhu, Lingjun; Chu, Haiyan; Gu, Dongying; Zhang, Zhengdong; Du, Mulong; Wang, Meilin
Highlights: 2-MeO-E1 and rs165599 in COMT were associated with colorectal cancer risk. The rs165599 G allele decreased the binding ability of miR-22-3p to COMT . COMT is highly expressed in colorectal cancer and affects the cellular phenotypes. Abstract: Objective: The different incidence of colorectal cancer between the sexes suggests that sex hormones may be involved in the susceptibility to colorectal cancer. The association between sex hormones and genetic variants in hormone metabolic pathways and the colorectal cancer risk remains unclear. Methods: We detected sex hormone levels in plasma from colorectal cancer patients and controls in males by ultra-high-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). We evaluated the clinical significance of sex hormones on colorectal cancer diagnosis with the area under the receiver operating characteristic curve (AUC). The role of genetic variants in hormone metabolic pathways in the colorectal cancer risk was assessed by a logistic regression model. The biological functions were detected by luciferase reporter assays and cell behavior experiments. Results: We found that 2-methoxyestrone (2-MeO-E1) was highly expressed in cases ( P FDR = 3.48 × 10 −19 ). The expression of 2-MeO-E1 in plasma showed improved accuracy for predicting colorectal cancer (AUC = 0.88). In the 2-MeO-E1 metabolic pathway, rs165599 in COMT was significantly associated with an increased risk of colorectal cancer ( P = 0.009). Mechanistically, we found that the rs165599 G allele could decrease the binding ability of miR-22-3p to the COMT 3′-UTR. Furthermore, knockdown of COMT inhibited cell proliferation, induced cell apoptosis and arrested the cell cycle in the G1 phase. Conclusion: This is the first study to show that 2-MeO-E1 and a genetic variant in COMT contribute to the susceptibility to colorectal cancer. These results shed light on the different incidence of colorectal cancer between the sexes.